The effects of an indigenous contraceptive herbal Formulation on the gonadotrophs of the pituitary gland Of rat (experimentat immunohistochemical research) - Sulaiman, Siti Amrah; Kapitonova, Marina Yu; Jamalullail, Syed Mohsin S. (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Objective: To observe the morphometric changes of the gonadotrophs and the plasma concentrations of follicle stimulating hormone and leutinizing hormone. Methodology : Thirty five animals were randomly divided into 5 groups. Control animals were given vehicle and experimental animals were given combined herbal extract or individual herbal extract at a dose of 540 mg/kg/day s.c for 7 days. Immune-stained gonadotrophs were studied by using image analyzer, FSH and LH serum concentrations were determined. Results: The FSH and LH concentrations were low in animals that received combined herbal extract (p<0.01) . FSH concentration was noted to be significantly low in animals that received P. rotundifolia (p<0.05). The mean cell area and cell density of gonadotrophs of animals that received combined herbal extract were significantly low compared to control group (p<0.05). Discussion : These findings were corresponded to our previous findings that the combined herbal extract reduced both estradiol and progesterone concentrations and the individual plant extracts reduced the estradiol concentration significantly but not the progesterone. Conclusion: We concluded that the herbal extracts do affect the pituitary gonadotrophs and the circulating gonadotrophins. Further evaluation is needed to verify whether the effect was directly on the pituitary or through a higher centre such as the hypothalamus.